Obstacles To Development Of Gayo Arabica Coffee Commodity In Bener Meriah Regency - Emmia Tambarta Kembaren; Nola Windirah (Journal of Agri Socio Economics and Business, 2021)
Coffee has great potential to be developed in Indonesia because of its large role in increasing the country's foreign exchange through export activities. Bener Meriah Regency, Aceh Province, is one of the main producing areas of Arabica coffee. The development of Arabica coffee commodities in Bener Meriah is still not optimal due to the findings of various problems such as post-harvest handling cultivation systems, technology, to marketing conditions that continue to change according to global conditions. This problem causes Bener Meriah Arabica coffee to not be optimal in contributing to regional income, employment and contributing to coffee farmers' household income. In the previous research, only one aspect highlighted, so the findings to overcome these problems have not been optimal. Through the analysis of Urgency, Seriousness, Growth (USG), this research will find a solution formed in stages of solving the problems experienced by Arabica coffee farmers, starting from the upstream to the downstream process. The results of the study show that the constraints on trade conditions that have changed after the Pandemic are the main problems that must be resolved first in Bener Meriah Regency. The second problem that must be resolved is extreme climate change. The third is post-harvest handling and the fourth is the high cost of transportation.